Effects of heavy metals and hyporheic exchange on microbial community structure and functions in hyporheic zone. (1st February 2022) - Liang, Dong; Song, Jinxi; Xia, Jun; Chang, Jianbo; Kong, Feihe; Sun, Haotian; Qiong wu,; Cheng, Dandong; Zhang, Yixuan
Abstract: The responses of microbial communities in hyporheic zone to the eco-hydrological process have been a hotspot in river ecological health research. However, the impact of different metal pollution levels and hyporheic exchange on the microbial communities are still unclear. In this study, we further explored the effects of different degrees of heavy metals pollution and the strength of hyporheic exchange on the structures and functions of microbial community in hyporheic zone sediment ecosystem. Sediments were collected from the Weihe River to determine the concentrations of heavy metals, grain size distribution, and hydraulic conductivity, and the microbial information were obtained by eDNA technology. The comprehensive pollution status of the study area was at the slight and moderate level. The hydraulic conductivity ( K v ) varied between 0.20 and 3.65 (m/d). The microbial community structures had complex temporal and spatial heterogeneity. The microbial molecular ecological network had modular characteristics and significant differences in different periods ( p  < 0.05). Metabolic functional genes in microbial communities had the highest relative abundance. In particular, there is a significant negative correlation between heavy metals and microorganisms ( p  < 0.05), with Cu and Zn contributing the most to microbial community changes ( p  < 0.05). Moreover, grain size had a significant impact on microorganisms, heavy metals and grain size significantly affect the predictive functions of microbial communities. Our in-depth research on microorganisms in the hyporheic zone provides references for monitoring and bioremediation of aquatic ecosystems. Highlights: Heavy metals and grain size had significant effects on functions of microorganisms. Heavy metal pollutants in hyporheic zone will pose certain ecological risks. Microbial community structure and hydraulic conductivity had seasonal fluctuation. Cu and Zn contributed the most to variations of microbial communities. Ni, Cu, Zn and Pb had negative effects on the abundance of certain microbial taxa.